How can Educational Leaders Promote Greater Student Engagement Remotely During COVID-19 - Hilliard, Ann Toler; Foose, Renee (Advances in Social Sciences Research Journal, 2020)
This study has been presented in order to share information as to how educational leaders can promote a greater opportunity for student engagement remotely during the COVID-19 crisis. Adjusting in more ways than one during COVID-19 has been challenging for many students and faculty members at universities globally. The leader sets the tone while working and sharing with faculty members ways to engage students at an adequate level to continue student learning experiences remotely. Adaptability and adjustments that most students and faculty members are making during this crisis have been notable by families and community leaders. With educational leaders taking the lead, the major emphasis for this study was to focus on best practices for engaging students in the most productive ways during the COVID-19 crisis.